2016
DOI: 10.4081/monaldi.2006.563
|View full text |Cite
|
Sign up to set email alerts
|

Pedunculated solitary fibrous tumours arising from the pleura

Abstract: Solitary fibrous tumour (SFT) is one of the rare tumours which arise from visceral pleura. Klemperer and Rabin first described SFT as a distinct clinical entity among primary pleural tumoUrs in 1931. Approximately 820 cases have been reported in literature to date. The management of patients with SFT is complete resection of the tumour and follow up of the patient to detect any possible late recurrence. In the present paper, we report two cases of pedunculated solitary fibrous tumours of the pleura that appear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 10 publications
0
1
0
1
Order By: Relevance
“…However, subsequent studies using immunohistochemical techniques and electron microscopy have shown that SFT originates from dendritic mesenchymal cells that are CD34-positive and capable of differentiating into fibroblasts, myofibroblasts, and vascular epithelial cells. [5][6][7] Although SFT can occur in various locations in the body, primary bladder SFT is rare, and patients may present with urinary symptoms and pelvic compression or be asymptomatic. In this case, the diagnosis was incidental during the evaluation of other diseases, and the patient did not have significant urinary symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…However, subsequent studies using immunohistochemical techniques and electron microscopy have shown that SFT originates from dendritic mesenchymal cells that are CD34-positive and capable of differentiating into fibroblasts, myofibroblasts, and vascular epithelial cells. [5][6][7] Although SFT can occur in various locations in the body, primary bladder SFT is rare, and patients may present with urinary symptoms and pelvic compression or be asymptomatic. In this case, the diagnosis was incidental during the evaluation of other diseases, and the patient did not have significant urinary symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…CT 呈现肋骨压迹的胸膜孤立性纤维性肿瘤 1 例分析 王继芳,姚以刚,石振东,何永满 沈阳医学院附属铁法煤业集团总医院,辽宁铁岭,中国 通讯作者:石振东,Email:szd666888@163.com 【摘要】目的 探讨胸膜孤立性纤维性肿瘤(SFTP)的临床、影像学特征及诊治方法。方法 回顾性分析 1 例 CT 呈现肋骨 压迹的胸膜 SFT 的诊断过程, 并复习有关文献。 结果 该患者无明显临床症状; 胸部 CT 示右侧后上胸壁胸膜外见一个约 3.4cm ×2.4cm 大小的类圆形软组织密度影,边界与胸膜分界不清,临近肋骨有压迹形成,增强扫描病灶强化稍不均匀,灶内可见 小斑片状低强化影;病理检查示肿瘤组织主要由梭形细胞组成,免疫组织化学示 CD34、CD99、SMA 阳性。结论 SFTP 是 一种少见的梭形细胞肿瘤,临床表现及影像学检查无特异性,CT 呈现肋骨压迹并非神经源性肿瘤的专有特征,诊断主要依 靠病理及免疫组织化学检查,手术治疗是首选的治疗方法,术后预后较好。 【关键词】纤维瘤;胸膜肿瘤;计算机断层扫描;免疫组织化学;鉴别诊断 孤立性纤维性肿瘤(solitary fibrous tumor,SFT)是一种少见的间叶源性梭形细胞肿瘤,由 klemperer 和 Rabin 首次描述 [1] ,曾称为"胸膜下纤维瘤"、"间皮下纤维瘤"和"局限性纤维性间皮瘤"等,国外文献 报道其发病率仅为 28/10 万,最常见的发病部位是脏层胸膜 [2] 。由于该病发现前常无明显症状,而在体检 [3] ,但曾有家族性发病的报道。最初认为 SFT 起源于间皮细胞,随着组织学、免 疫组织化学、电镜、分子生物学技术的发展和应用,目前研究显示 SFT 发生与间皮并无关联,并已证实 SFT 起源于一种 CD34 阳性的树突状间叶细胞,具有向纤维母细胞、肌纤维母细胞、血管外皮细胞及血管内皮 细胞分化的特性 [4] 。SFT 多为良性或交界性,恶性者仅占 20% [5] ,常为单发,偶而多发,约 80%见于胸膜, 胸膜外其他结缔组织也可发生,以皮下软组织、眼眶、颅内及盆腔多见 [6] 。临床症状依发生部位和肿瘤大 小不同而异, 多数患者表现为局部缓慢性生长的无痛性肿块, 当肿块巨大累及重要脏器时可出现相应症状。 发生于中枢神经系统的 SFT,因肿瘤阻碍脑脊液回流,可出现颅高压的表现。少数患者可伴有肺性肥大性 骨关节病 [2] 、顽固性低血糖(3%~4%) [7] 、杵状指(趾)及胸腔积液 [8] 。…”
unclassified